A near-infrared light-controlled system for reversible presentation of bioactive ligands using polypeptide-engineered functionalized gold nanorods1. Issue 13 (14th February 2015) - Yang, Jie; Yao, Ming-Hao; Du, Ming-Shuo; Jin, Rui-Mei; Zhao, Dong-Hui; Ma, Jun; Ma, Zhi-Ya; Zhao, Yuan-Di; Liu, Bo
<x xml:space="preserve">Abstract</x> A hybrid platform with polypeptide-engineered functionalized gold nanorods has been designed for reversible presentation of immobilized bioactive ligands by near-infrared light.